Estimation of propulsive forces acting on a hand using pressure measurement and underwater motion capture during front crawl swimming - Tsunokawa, T.; Narita, K.; Mankyu, H.; Ogita, F.; Takagi, H. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
This study aimed to estimate hand propulsive force during the front crawl and to clarify its relationship with swimming velocity. Eight male swimmers performed 16-m front crawl ten times at various velocities. During trials, pressure measurement and underwater motion capture were used jointly to analyse hand kinematics and fluid forces. Six pressure sensors were attached to the right hand, and reflective markers were attached to landmark points on the right hand and hip. A motion capture system composed of 15 underwater cameras was used. Fluid forces were estimated by multiplying the projected areas and the pressure differences between the palm side and dorsal side of the right hand. Acting directions of fluid forces were analysed using a normal vector perpendicular to the right hand. Fluid forces acting in the propulsive direction were defined as propulsive forces, and the proportion of propulsive forces among the resultant forces was defined as the Froude efficiency. At maximal recorded velocity (1.58 ± 0.06 m/s-1), resultant force was 56.4 ± 10.5 N, propulsive force was 44.6 ± 9.0 N, and Froude efficiency was 79.1 ± 8.5. As reported in previous studies, propulsive forces increased with swimming velocity. In some swimmers, the propulsive forces increased in proportion to the cube of swimming velocity. Froude efficiency also increased as swimming velocity increased because propulsive forces increased with swimming velocity, whereas forces acting in directions other than the propulsive direction did not.